Estrategias de fortalecimiento de clima laboral para los colaboradores de la empresa de embutidos La Madrileña. - Vega Toaquiza, Myrian Patricia (2023)
This study aimed to design Strategies to Strengthen the Labor Climate in the La Madrileña, Sausage Company, where quantitative research was carried out with a non-experimental cross-sectional approach, using instruments validated by authors to evaluate the eight dimensions of the Work Climate; the results reflected a positive evaluation in seven of the eight dimensions, and in Job Satisfaction indicator a moderate-low level was presented. To address this problem, strategies were designed, including periodic surveys of job satisfaction, employee recognition and rewards, a positive and motivating environment in the workplace, and team-building activities. This research proposal aims to establish a flexible and innovative business culture where open communication, mutual respect, active participation, and employee satisfaction are the fundamental axes for work motivation, increased productivity, and better general performance in the company. Finally, La Madrileña, Sausage company, was recommended to improve its Work Environment continuously.